The Nature Of The Orientations Of Achievement Responsibility Among Students Of The First Year Of Secondary Education At Othman Bin Affan Secondary School In The City Of M’sila - Ali Raqiq , Ali; abd_elhafidhi, yahia (El Omda in Linguistics and Discourse Analysis, 2024)
The current study based on the exploratory approach aimed to find out the ature of the orientations of achievement responsibility among students of the first year of secondary education at Othman bin Affan High School in the city of M'sila And examine the significance of the differences in achievement esponsibility among the members of the study population according to the gender variable and the study division, for this purpose the scale of achievement responsibility was applied to Al-Khazaala and Al-Hamdoun, and the psychometric properties of the scale were verified after applying it to an exploratory sample that was selected in a simple random way from the current study population, To test the hypotheses of the study, the data were collected and analyzed statistically.The study resulted in the following results: External orientations of achievement responsibility among students of the first year of secondary education. There were no differences in achievement responsibility due to the gender variable and the division of study among students in the first year of secondary education.